2016
DOI: 10.1080/15592294.2016.1179411
|View full text |Cite
|
Sign up to set email alerts
|

Validation of differential GDAP1 DNA methylation in alcohol dependence and its potential function as a biomarker for disease severity and therapy outcome

Abstract: Alcohol dependence is a severe disorder contributing substantially to the global burden of disease. Despite the detrimental consequences of chronic alcohol abuse and dependence, effective prevention strategies as well as treatment options are largely missing to date. Accumulating evidence suggests that gene-environment interactions, including epigenetic mechanisms, play a role in the etiology of alcohol dependence. A recent epigenome-wide study reported widespread alterations of DNA methylation patterns in alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 62 publications
2
18
0
Order By: Relevance
“…Methylation at the second most powerfully predictive site used in our three marker assay set, cg02583484, was the second‐ranked probe in the 2016 Liu meta‐analyses. Finally, methylation at cg23779890, one of the loci for which we were unable to construct a ddPCR assay, has been independently shown to be associated with alcohol use status by Nieratschker and colleagues, as well as Liu and colleagues work (Brückmann et al, ; Liu et al, ). Hence, there is reason for optimism.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Methylation at the second most powerfully predictive site used in our three marker assay set, cg02583484, was the second‐ranked probe in the 2016 Liu meta‐analyses. Finally, methylation at cg23779890, one of the loci for which we were unable to construct a ddPCR assay, has been independently shown to be associated with alcohol use status by Nieratschker and colleagues, as well as Liu and colleagues work (Brückmann et al, ; Liu et al, ). Hence, there is reason for optimism.…”
Section: Discussionmentioning
confidence: 81%
“…Third, and most importantly, the reversion curve for methylation status as a function of abstinence needs to be established. Reversion of substance‐induced changes has already been documented for both cigarette and alcohol‐associated methylation changes (Bauer et al, ; Brückmann et al, ; Philibert et al, ; Philibert et al, ; Wilson et al, ). However, this preliminary understanding of the reversion process is woefully short of the knowledge base needed to monitor the effectiveness and guide the improvement of existing therapies.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Recent studies have begun to combine genome‐wide analysis of DNA methylation with that of intriguing phenotypic metrics. For instance, a recent study confirmed a genomewide report of hypomethylation at the ganglioside‐induced differentiation‐associated protein 1 ( GDAP1 ) gene and further found that GDAP1 DNA methylation was significantly associated with severity of patient with AUD (Brückmann et al., ). Another recent study examined DNA methylation in monozygotic twins with discordant AUD status and complemented this work with personality evaluation and MRI imaging during an impulsiveness task (Ruggeri et al., ).…”
Section: Dna Methylation In Human Alcoholicsmentioning
confidence: 75%
“…Unfortunately, this type of approach resulted in the inclusion of individuals who used substances at an earlier point in their life, but may have become abstinent for as many as 10–20 years. Since subsequent analyses have clearly shown that methylation signatures associated with substance use consumption may revert, sometimes rather rapidly, to baseline values (Bauer et al, ; Brückmann, Di Santo, Karle, Batra, & Nieratschker, ; Philibert et al, ), this lack of understanding resulted in the inclusion of individuals whose methylation signatures may have more resembled the “unaffecteds” in the “affected” category. Subsequent appreciation of the pliability of the methylome has led to improvements in both the chronological and quantitative consumption phenotyping of subjects used in epigenetic studies.…”
Section: Introductionmentioning
confidence: 99%